General interests of host states in international investment law - Sacerdoti, Giorgio; Acconci, Pia; Valenti, Mara; De Luca, Anna (New York : Cambridge University Press, 2014)
'Signatory States have the right to take action in order to maintain their financial stability, stimulate economic development or further their non-economic interests (such as health, the environment and food security). However, such measures can potentially conflict with the rights of foreign investors. Regulators and policy makers must take States' international commitments toward foreign investors into account when making decisions. They must also avoid resorting to protectionism in drafting new treaties. With this tension in mind, this book offers a balanced reappraisal of bilateral treaties and regional agreements on foreign investments. The sensitive issues are examined in the light of the case law of arbitral investment tribunals and other international courts, and the analysis highlights how cross-fertilisation between trade and investment can assist in resolving conflicts'--
Machine generated contents note: Part I. General Interests of Host States in the Application of Investment Treaties: 1. The application of BITs in time of economic crisis: limits to their coverage, necessity and the relevance of WTO law Giorgio Sacerdoti; 2. The protection of general interests of host states in the application of the fair and equitable treatment standard Mara Valenti; 3. Indirect expropriations and regulatory takings: what role for the'legitimate expectations' of foreign investors? Anna De Luca; 4. Trade and investment law: what relations? Friedl Weiss; 5. On the evolution and slow convergence of international trade and investment law Jurgen Kurtz; 6. Sovereign wealth funds as protected investors under BITs and the safeguard of the national security of host states Michele Barbieri; Part II. The Protection of Non-investment Concerns in International Investment Law: 7. The integration of non-investment concerns as an opportunity for the modernization of international investment law: is a multilateral approach desirable? Pia Acconci; 8. Intellectual property protection in investment agreements and public concerns Antonietta Di Blase;; 9. Up-keeping non-economic values in development assistance. Does the World Bank practice what it preaches? Answers from the Inspection Panel Agostina Latino; 10. The protection of indigenous peoples concerns in the World Bank-funded projects Martina Guidi; Part III. The Protection of General Interests of Host States and the EU as a New Player in the Investment Arena: 11. The future of BITs between EU member states: are intra-EU BITs compatible with the internal market? Paola Mariani; 12. European Union restrictions to the free movement of capital vs. BITs guarantees: learning from the European Court of Justice case law Elsa Milanesi; 13. Ensuring the consistency of the EU investment policy within the EU external action: the relevance of non-trade values Alessando Perfetti; 14. Non-financial concerns in the lending policy of the European Investment Bank in context Emanuela Pistoia; Part IV. The Protection of General Interests of Host States in the Trade and Investment Context: Other Regional Perspectives: 15. The protection of general interests of host states in regional agreements in the Asia-Pacific area Claudio Dordi; 16. Domestic policies and international investment agreements in MERCOSUR countries Arno Dal Ri and Paulo De Alc{u386E}tara Veloso; Part V. The Protection of General Interests of Host States from the Italian Perspective: 17. Italy's treaty practice and case law: what balance between investors' protection and general interests of states? Federico Ortino and Domenico Di Pietro; 18. Diplomatic intervention and state-to-state arbitration as alternative means for the protection of foreign investments and host states' general interests: the Italian experience Matilde Recanati.
Includes bibliographical references and index.
Keywords: Investments, Foreign (International law); Investments, Foreign -- Law and legislation; International commercial arbitration